2010
DOI: 10.5014/ajot.64.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Violations Versus Driving Errors of Older Adults: Informing Clinical Practice

Abstract: Certain driving errors are predictive of crashes, but whether the type of errors evaluated during on-road assessment is similar to traffic violations that are associated with crashes is unknown. Using the crash data of 5,345 older drivers and expert reviewers, we constructed a violation-to-error classification based on rater agreement. We examined the effects of predictor variables on crash-related injuries by risk probability using logistic regression. Drivers' mean age was 76.08 (standard deviation = 7.10); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…In the present study, certain driving errors were more common than others in the older drivers group, e.g. speed adjustment and positioning, and these errors do predict crashes in older drivers [32,33] . Furthermore, and similar to our findings, Reason et al [31] found frequent driving errors regarding gear changing.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, certain driving errors were more common than others in the older drivers group, e.g. speed adjustment and positioning, and these errors do predict crashes in older drivers [32,33] . Furthermore, and similar to our findings, Reason et al [31] found frequent driving errors regarding gear changing.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, there is an opportunity for refinement of the current scoring approach to enable determination of how much a given difference in scores matters from a safety viewpoint. Recent work by Classen and colleagues (Classen, Shechtman, Awadzi, Joo, & Lanford, 2010) will be useful for advancing the measurement of driving errors and associated safety effects. Their findings demonstrated a hierarchy of importance of errors in predicting crash-related injury with highest probability for injury associated with lane maintenance, yielding, and gap acceptance errors; moderate associations with speed regulation; and vehicle positioning and adjustment to stimuli conferring a low probability.…”
Section: Discussionmentioning
confidence: 99%
“…These findings presented a classification structure that may serve as a link from errors during driving evaluation to the contributing factors of at-risk motor vehicle collisions reported in police reports (Classen, 2010). Unique to this study, our comparison of assistance to class of errors also illustrates that explicitly documented assistance corresponded to relatively few of the total enumerated errors in reports.…”
Section: Percentages Of Assistance Linked To Error Classes and On-rmentioning
confidence: 59%